Physiochemical parameters optimization for enhanced nisin production by Lactococcus lactis (MTCC 440) - Puspadhwaja Mall; Bijaya Kumar Mohanty; Dhananjay Bhawanishankar Patankar; Rustom Mody; Rashbehari Tunga (Brazilian Archives of Biology and Technology, 2010)
The influence of various physiochemical parameters on the growth of Lactococcus lactis sub sp. lactis MTCC 440 was studied at shake flask level for 20 h. Media optimization (MRS broth) was studied to achieve enhanced growth of the organism and also nisin production. Bioassay of nisin was done with agar diffusion method using Streptococcus agalactae NCIM 2401 as indicator strain. MRS broth (6%, w/v) with 0.15μg/ml of nisin supplemented with 0.5% (v/v) skimmed milk was found to be the best for nisin production as well as for growth of L lactis. The production of nisin was strongly influenced by the presence of skimmed milk and nisin in MRS broth. The production of nisin was affected by the physical parameters and maximum nisin production was at 30(0)C while the optimal temperature for biomass production was 37(0)C.